(untitled) (Sport and Exercise Psychology, 2025)
"The Art and Science of Talent in Figure Skating: An Integrated Approach" provides a critical review of the latest research on talent development in figure skating, analyzing 20 studies published after the 2022 Olympic Games. Beyond examining key factors such as performance prediction, early specialization, and stress management, the study focuses on actionable insights for athletes, coaches, and federations. It highlights how a more balanced approach to training and talent selection can extend athletic careers, reduce burnout risk, and enhance overall performance. Additionally, it delves into the role of judging systems, proposing strategies to refine scoring criteria and ensure fairer, more transparent competition. The findings offer concrete recommendations for implementing athlete development programs, psychological support systems, and sustainable sport policies—ultimately fostering a competitive environment that values both technical excellence and artistic expression.